Performance evaluation on fixed water-based firefighting system in suppressing large fire in urban tunnels. (February 2019) - Li, J.; Li, Y.F.; Bi, Q.; Li, Y.; Chow, W.K.; Cheng, C.H.; To, C.W.; Chow, C.L.
Highlights: Water-based fixed firefighting (WFFF) systems are installed in many road tunnels. Operating WFFF system might affect performance of longitudinal ventilation system. Performance of WFFF systems with and without shields to fire source were evaluated. Test results under 20 MW diesel pool fires or wood pallet fires are reported. Abstract: Operating fixed water-based firefighting systems (FFFS) might affect the performance of other parts of an integrated tunnel safety system, particularly the longitudinal ventilation system. The interaction of the water spray discharged from two FFFS (with and without foam), with the longitudinal ventilation system in a new city tunnel under construction was studied by full-scale burning tests. Results of the study under large fires up to 20 MW in diesel pool fires or wood pallet fires are reported in this paper. The impact of longitudinal ventilation, the activation sequences of the ventilation system and the fixed fire-fighting system, and the performance of the two FFFS in suppressing vehicular fires with and without shields to fire sources were evaluated. Results are expected to be useful for drafting appropriate fire codes on fire suppression systems for controlling urban tunnel fires.